Social policy in the European Union: state of play 2016 (Brussels, 2017)
"This book develops a new approach for estimating the way in which labour costs reflect cost competitiveness. Conventionally, unit labour costs (a standard measure of cost competitiveness) are calculated as indices, without regard to the relative levels of wage costs. To remedy this, the authors develop the concept of the ‘equilibrium wage’, which corresponds to the level of wages when the returns on capital in different regions and sectors are equalised. A wage competitiveness indicator is thus calculated as the ratio of actual to equilibrium wages.